PENERAPAN KONSELING QUR’ANI UNTUK MENGENTASKAN ADAB BURUK GENERASI MILENIAL PADA SISWA SMPN 1 SURALAGA - Nusuki, Nusuki; Sulistiana, Herlina (JKP (Jurnal Konseling Pendidikan), 2023)
This thesis discusses the phenomenon of bad manners that occurs among the millennial generation which is caused by the influence of technological advances and  how to apply Qur'anic counseling that uses repentance therapy in alleviating these bad manners. This study also aims to find out how the effectiveness of the application of Qur'anic Counseling by using repentance therapy carried out through group counseling services. The results of this study indicate that the initial phase data (A1) before being given treatment (pretest) in the form of Qur'anic counseling with repentance therapy obtained a maximum score of 128 with an average mean of 25.6 which shows bad manners of students in the bad category. During the intervention phase (B) the score decreased to 83 with an average of 16.6 indicating a slightly poor category. Then after being given an intervention (B2) the score decreased to 59 with an average mean of 11.8 which indicates that the students' bad manners are not bad